Adaptive management in restoration initiatives: Lessons learned from some of South Africa's projects - (:unkn) unknown (My University, 2021)
Land use change, coupled with rapid human population growth, has increased ecosystem degradation, giving rise to ecosystem restoration initiatives worldwide. We conducted an assessment and reflection using a feedback framework for strategic adaptive management in three woodland restoration initiatives in South Africa. This is because assessment and reflection are critical components for successful strategic adaptive management. We found that the three restoration initiatives have had a limited emphasis on sustainable livelihood-driven outcomes, because the initiatives mainly aimed to restore biodiversity, ecosystem infrastructure and ecosystem services. Consequently, we propose a modified livelihood framework that suggests a more inclusive approach towards achieving positive human outcome-driven restoration of degraded woodlands. Based on the framework, we emphasise that restoration initiatives should seek to invest in ecosystem restoration in the context of sustainable development goals, to enhance people's livelihoods, and climate change mitigation and adaptation. Harmonizing the competing needs for resource allocation, sustainable interventions and livelihoods sustenance will be important, given the limited extent of alternative locally based livelihood options in the rural disadvantaged areas. This is because most of the rural population is largely dependent on woodland ecosystem services for their livelihoods. We then suggest that to ensure that human-driven outcomes are also equally prioritised; the assessment, reflection and feedback framework and the livelihoods framework should form part of restoration initiatives.
Keywords: African Research